2020
DOI: 10.1111/jcmm.15584
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting aberrations of SNRPN, ZAC1 and INPP5F genes involved in the pathogenesis of congenital heart disease with extracardiac malformations

Abstract: Congenital heart disease (CHD) with extracardiac malformations (EM) is the most common multiple malformation, resulting from the interaction between genetic abnormalities and environmental factors. Most studies have attributed the causes of CHD with EM to chromosomal abnormalities. However, multi‐system dysplasia is usually caused by both genetic mutations and epigenetic dysregulation. The epigenetic mechanisms underlying the pathogenesis of CHD with EM remain unclear. In this study, we investigated the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A role for methylation and imprinting abnormalities in the etiology of structural birth defects is consistent with the occurrence of such conditions in imprinting syndromes (e.g., omphalocele in Beckwith-Wiedemann syndrome) 83 , 93 and has been suggested based on studies of non-syndromic structural birth defects. 94 , 95 , 96 , 97 Further, epigenetic and imprinting differences resulting from ARTs have been suggested as a potential cause for the increased risk of structural birth defects in offspring conceived by in vitro fertilization or intracytoplasmic sperm injection. 98 , 99 Consequently, it may be that any association between structural birth defects and MEGs is limited to the subset of MEGs that are involved in methylation and imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…A role for methylation and imprinting abnormalities in the etiology of structural birth defects is consistent with the occurrence of such conditions in imprinting syndromes (e.g., omphalocele in Beckwith-Wiedemann syndrome) 83 , 93 and has been suggested based on studies of non-syndromic structural birth defects. 94 , 95 , 96 , 97 Further, epigenetic and imprinting differences resulting from ARTs have been suggested as a potential cause for the increased risk of structural birth defects in offspring conceived by in vitro fertilization or intracytoplasmic sperm injection. 98 , 99 Consequently, it may be that any association between structural birth defects and MEGs is limited to the subset of MEGs that are involved in methylation and imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies reported that SNHG14 and SNRPN are involved in the pathogenesis of cardiac hypertrophy and CHD, respectively. 27 , 28 These results indicated that A-to-I editing events during cardiomyocyte differentiation may also be related to cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 85%
“…Another study on aberrations imprinting genes involved in the pathogenesis of CHD with extracardiac malformations also found the hypermethylation of INPP5F. In addition, risk analysis showed that abnormal hypermethylation of SNRPN and ZAC1 resulted in 5.545 and 7.438 times higher risks of CHD with extracardiac malformations [ 144 ].…”
Section: Dna Methylation Orchestrates Cardiomyocyte Development Maturation and Diseasementioning
confidence: 99%